Inhibition mechanism of SARS-CoV-2 main protease by ebselen and its derivatives - Kangsa Amporndanai (Nature Portfolio, 2021)
Ebselen is an organoselenium drug that inhibits the SARS-CoV-2 main protease (Mpro). Here, the authors co-crystallised Mpro with ebselen and an ebselen derivative and observed an enzyme bound organoselenium covalent adduct in the crystal structures, which was also confirmed by mass spectrometry analysis.